1994
DOI: 10.1097/00000658-199410000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Vagotomy, Antrectomy, and Roux-en-Y Diversion for Complex Reoperative Gastroesophageal Reflux Disease

Abstract: ObjectiveFailure of conventional surgical therapy for treatment of patients with gastroesophageal reflux disease (GERD) taxes the ingenuity of the esophageal surgeon. This study defines the role of vagotomy, antrectomy, and Roux-en-Y diversion coupled, when necessary, with resection of the esophagogastric junction as an alternative to other surgical procedures currently employed for these complicated cases. Summary Background DataCurrently, the operation in question rarely is performed in the United States. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…[74][75][76] Ellis et al, 77 in 1996, reported on 101 patients reoperated on for recurrence of esophagitis, and suggested that the best choice is the acid suppression-bile diversion procedure. In our experience, and in agreement with other publications, this alternative appears to be the best and gives the most permanent results [78][79][80] in comparison with the classic fundoplication or its variants such as the Collis-Nissen, Belsey-Collis, or Thal-Nissen procedures. 81 Partial esophageal resections with esophagus gastroanastomosis, colon interposition, or total esophagectomy are operations that have been indicated by other authors for patients with complicated Barrett's esophagus with non-dilatable strictures.…”
Section: Discussionsupporting
confidence: 91%
“…[74][75][76] Ellis et al, 77 in 1996, reported on 101 patients reoperated on for recurrence of esophagitis, and suggested that the best choice is the acid suppression-bile diversion procedure. In our experience, and in agreement with other publications, this alternative appears to be the best and gives the most permanent results [78][79][80] in comparison with the classic fundoplication or its variants such as the Collis-Nissen, Belsey-Collis, or Thal-Nissen procedures. 81 Partial esophageal resections with esophagus gastroanastomosis, colon interposition, or total esophagectomy are operations that have been indicated by other authors for patients with complicated Barrett's esophagus with non-dilatable strictures.…”
Section: Discussionsupporting
confidence: 91%
“…We have now performed this with success on three occasions with good results (one of these is from this series with a preoperative Visick IV, Table 3) after this redo surgery she is now Visick I. 21,22 There were three of 35 (12%) who required a second reoperation which is similar to the frequency that is reported by the Emory group. 17 While we accept that a follow-up of a year may give a false impression of results, in common with surgeons from Atlanta, we have found it difficult to obtain follow-up greater than 1 year in meaningful numbers of patients.…”
Section: Discussionsupporting
confidence: 72%
“…For those few patients who have continued, documented reflux following redo laparoscopic antireflux surgery, antrectomy and Roux‐en‐Y reconstruction may be an alternative to further attempts at hiatal surgery, reducing the risk of iatrogenic visceral injury. We have now performed this with success on three occasions with good results (one of these is from this series with a preoperative Visick IV, Table 3) after this redo surgery she is now Visick I 21,22 . There were three of 35 (12%) who required a second reoperation which is similar to the frequency that is reported by the Emory group 17 .…”
Section: Discussionsupporting
confidence: 71%
“…9,10 Many have employed this operation as a solution after recurrence of symptoms following a classic antireflux operation (360 Nissen fundoplication or cardial calibration with posterior gastropexy) or in selected patients with ulcer or strictures as complications of reflux esophagitis. [11][12][13][14][23][24][25] This procedure has been used as a primary operation for complicated Barrett's esophagus by Fekete and others with excellent results. [26][27][28][29] Washer et al prospectively compared Nissen fundoplication versus antrectomy plus Roux-en-Y gastrojejunostomy in patients with severe esophagitis and reported good results in 65% after Nissen fundoplication versus 95% after acid suppression bile diversion techniques (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The results of several recent prospective studies suggest that the acid‐suppression duodenal diversion surgery abolishes acid and duodenal reflux into the esophagus and gives excellent results in patients with long‐segment Barrett's esophagus 9,10 . Many have employed this operation as a solution after recurrence of symptoms following a classic antireflux operation (360 Nissen fundoplication or cardial calibration with posterior gastropexy) or in selected patients with ulcer or strictures as complications of reflux esophagitis 11–14,23–25 . This procedure has been used as a primary operation for complicated Barrett's esophagus by Fekete and others with excellent results 26–29 .…”
Section: Discussionmentioning
confidence: 99%